Comparative Analysis of Pro-Environmental Behavior Among Junior High School Students in Samarinda: Public vs. Islamic Boarding Schools - Muliati Syam; Putri Sri Rahmawati; Atin Nuryadin (Unnes Science Education Journal, 2026)
Pro-environmental behavior (PEB) encompasses actions that prevent environmental harm and promote environmental health. This study aims to analyze the PEB of junior high school students in Samarinda based on school type, focusing on three key aspects: preservation, utilization, and appreciation. The research compares students from public junior high schools and Islamic boarding schools, while also exploring their environmental perceptions and how school type influences PEB. A quantitative comparative approach was used, sampling 290 ninth-grade students in Samarinda via purposive sampling and collecting data through questionnaires. Results showed that students from public schools had a lower PEB score (3.60) compared to those from Islamic boarding schools (3.67). Students in Samarinda generally exhibited a positive environmental perception. Statistical analysis indicated that school type significantly impacts PEB. The findings suggest that Islamic boarding schools may implement more effective environmental education practices than public schools, underscoring the need for public schools to adopt similar strategies. In conclusion, school type plays a key role in shaping students' environmental behavior, with Islamic boarding schools showing stronger outcomes. These results support the need for school-based environmental education tailored to specific contexts.